A recepção do mito de Heráclio por Gautier d’Arras - Souza, Guilherme Queiroz de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis analyzes the reception of the myth of the basileus Heraclius (ca. 575-641) by the French cleric Gautier d’Arras. In Eracle (late 12th century), tripartite octosyllabic romance (6570 verses), Gautier adapted the biographical trajectory of the Byzantine ruler, from his birth to his death. Especially in the third part of the work, the author was based in the Reversio Sanctae Crucis, liturgical text that popularized the Heraclian myth in the Western Christian imaginary. In Reversio, whose authorship was attributed to the Carolingian Rabanus Maurus, are celebrated the triumph of Heraclius against the Persians and the recovery of the relic of the Holy Cross and of Jerusalem. Initially we analyze the origin of the myth in three authors of the Western Early Middle Ages: two from “historical tradition” (Fredegar and Mozarabic Chronicler) and one from “legendary tradition” (Pseudo-Rabanus). Then, we enter into the core of the thesis, with the exam of the reception and “literarization” of the mythical figure of Heraclius by Gautier d’Arras. Influenced by a symbolic language, the cleric introduced the stages of the hero’s childhood/youth (1st part of the romance) and adapted the narrative of the Reversio (3rd part of the romance). With his literary talent and imaginative freedom, Gautier potentiated certain characteristics of the basileus and originally introduced others, which resulted in a singular character. In the same way, the “update” of Reversio content became the Byzantine ruler a more familiar man to the public of the 12th century

Esta tese analisa a recepção do mito do basileus Heráclio (c. 575-641) pelo clérigo francês Gautier d’Arras. Em Eracle (fim do século XII), romance octossilábico tripartite (6570 versos), Gautier adaptou a trajetória biográfica do soberano bizantino, do nascimento à morte. Especialmente na terceira parte da obra, o autor baseou-se na Reversio Sanctae Crucis, texto litúrgico que popularizou o mito heracliano no imaginário cristão ocidental. Na Reversio, cuja autoria era atribuída ao carolíngio Rábano Mauro, celebram-se o triunfo de Heráclio contra os persas e a recuperação da relíquia da Santa Cruz e de Jerusalém. Inicialmente analisamos o nascimento do mito em três autores da Alta Idade Média ocidental: dois da “tradição histórica” (Fredegário e o Cronista Moçárabe) e um da “tradição lendária” (Pseudo-Rábano). Depois, entramos no cerne da tese, com o exame da recepção e “literarização” da figura mítica de Heráclio por Gautier. Influenciado por uma linguagem simbólica, o clérigo introduziu as etapas da infância/juventude do herói (1ª parte do romance) e adaptou a narrativa da Reversio (3ª parte do romance). Com seu talento literário e liberdade imaginativa, Gautier potencializou determinadas características do basileus e originalmente inseriu outras, o que resultou num personagem singular. Da mesma forma, a “atualização” do conteúdo da Reversio tornou o governante bizantino um homem mais familiar ao público do século XII
Keywords: Gautier d'Arras, fl. séc. XII; Heráclio, Imperador Bizantino, ca. 575-641; Literatura medieval; Idade Media - Historia; Herois - Mitologia; History